Difficulties in the Prognostic Study of Oral Leukoplakia: Standardisation Proposal of Follow-Up Parameters - Saldivia-Siracusa, Cristina; González-Arriagada, Wilfredo Alejandro (Frontiers in Oral Health, 2021)
Oral leukoplakia is the most prevalent potentially malignant disorder of the oral cavity. To evaluate its potential for malignancy, appropriate documentation of the biological parameters is crucial, allowing the patients' progression to be assessed. We hypothesised a lack of standardisation in the parameters employed for the prognostic study of oral leukoplakia; our aims were to determine the different parameters used for follow-up according to definition, importance, and frequency of use, and to provide a standardisation proposal of follow-up research. We made a scoping review to identify papers with the keywords “leukoplakia”, “oral” and “follow-up” published until June 2019 in English, Spanish and Portuguese literature through an online search in PUBMED, SCIELO, and SCOPUS databases. In total, 514 articles were initially identified, and fifty-nine publications were selected, of which 37 were retrospective. The reports included a total of 18,660 patients between 13 and 98 years old, with a mean age of 57.6 years. Tobacco and alcohol habits were positive for 77% and 37% of the patients, respectively. Our results showed that reported leukoplakias were predominantly located on buccal mucosa (40.4%), were homogeneous (60.8%), multiple (59.9%), smaller than 2 cm (74.4%) and histopathologically non-dysplastic (71%). The mean follow-up time was 55 months, with a 13% malignant transformation rate. The categorisation and definition of multiple variables were notably diverse. Age, sex, habits (tobacco and alcohol), site, size, distribution, morphology, degree of dysplasia, and evolution were the chosen parameters for our proposal. The current study reflected the lack of consensus found in the literature regarding parameters for diagnosis or follow-up, impacting negatively on clinical and research results. Standardisation comprises an efficient way to facilitate the prognosis assessment of oral leukoplakia, being beneficial for clinical practice, and enabling better quality information to apply in research.